Pengembangan E-Modul IPAS untuk Meningkatkan Kemandirian Belajar Siswa kelas IV SD - Jefri Dwi Putra; Ulfia Rahmi (Universitas Negeri Padang, 2023)
This study seeks to develop dependable, simple, and effective e-module learning resources to meet the content and media feasibility requirements for social studies class IV SD N 12 Koto Baru. This method of research and development employs the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework. Participants included teachers, students, learning experts, media experts, and material experts. Included among the research methodologies were questionnaires and evaluation instruments. The two categories of data analysis techniques are quantitative analysis techniques and qualitative analysis techniques. On the product validity test, Validator I received an average score of 4.86 (